Evaluation of Reproductive Tract Cytokines in Post-partum Beef Cows Relating to Reproductive Microbiota and Fertility Outcomes - Poole, Rebecca K.; Ault-Seay, Taylor B.; Payton, Rebecca R.; Myer, Phillip R.; Lear, Andrea S.; Pohler, Ky G. (Frontiers in Animal Science, 2021)
The activity of the immune system in the reproductive tract has been proven to be crucial in the response to uterine diseases, normal reproductive functions, and tolerance to the allogeneic fetus during pregnancy. The objectives of the current study were to 1) evaluate uterine and vaginal cytokine concentrations in postpartum cows undergoing estrus synchronization followed by timed artificial insemination (TAI) and 2) correlate bacterial communities with cytokine concentrations. Postpartum Angus cows (n = 20) were subjected to a 7-Day Co-Synch protocol with pre-synchronization beginning 21 days prior (d -21) to TAI (d 0). Uterine and vaginal flushes were collected on d -21 and -2. Pregnancy was determined by transrectal ultrasound on d 30. Cytokines include interleukin (IL)-1b, IL-6, IL-10, transforming growth factor beta (TGF-β), and immunoglobin A (IgA) and concentrations were determined by commercial ELISA kits. No differences by day or pregnancy status in cytokine concentrations were detected in vaginal samples. No differences by day or pregnancy status in IgA, IL-10, or IL-1b concentrations were detected in uterine samples. Overall TGF-β concentrations in the uterus were greater in resulting pregnant than non-pregnant cows (44.0 ± 13.4 pg/mL vs 14.7 ± 4.9 pg/mL; P = 0.047). Uterine TGF-β was correlated with the relative abundance of genera Treponema (r = -0.668; P = 0.049) in resulting non-pregnant cows on d -21 and with the relative abundance of genera Ureaplasma (r = 0.901; P = 0.0004) in resulting pregnant cows on d -2. In resulting pregnant animals, a tendency for a strong correlation was detected between d -2 progesterone concentrations and uterine TGF-β concentrations (r = 0.591, P = 0.07). Overall IL-6 concentrations in the uterus were greater in resulting non-pregnant than pregnant cows (198.7 ± 21.8 pg/mL vs 144.3 ± 16.1 pg/mL; P = 0.045). A correlation was also detected between uterine IL-6 concentrations and the relative abundance of genera Butyrivibrio (r = 0.742; P = 0.022) in resulting non-pregnant cows on d -21. These results suggest possible relationships between different bacterial communities and cytokine concentrations within the uterus of beef cattle prior to TAI that may ultimately affect fertility outcomes.